2019
DOI: 10.1002/pc.25277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing parameters on the fabrication of fiber metal laminates by vacuum infusion process

Abstract: Fiber metal laminates (FMLs) are hybrid structures made of fibrous composite layers that are located between thin metal layers and joined together by resin. In the current fabrication process, FMLs require prepreg and use of an autoclave or press. This will increase the cost of production and limit the size of the piece to the dimensions of the autoclave or press. Hence, there is an interest in finding methods of construction that are affordable and have no dimensional limitations but also does not reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…GLAREs also showed high impact resistance, fatigue strength, superior corrosion, and fire resistance. [15][16][17][18] A unique possibility to enhance the overall characteristics of a sandwich material is accomplished through blending nanofillers in polymer while preparing the FRP plies. The blends of nanofillers enhances the specific physical properties of polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLAREs also showed high impact resistance, fatigue strength, superior corrosion, and fire resistance. [15][16][17][18] A unique possibility to enhance the overall characteristics of a sandwich material is accomplished through blending nanofillers in polymer while preparing the FRP plies. The blends of nanofillers enhances the specific physical properties of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The GLAREs reduced the weight of the structure and exhibited high mechanical and tribological properties. GLAREs also showed high impact resistance, fatigue strength, superior corrosion, and fire resistance 15–18 …”
Section: Introductionmentioning
confidence: 99%
“…They estimated the fiber volume fraction and void content of all the processed laminates $49% and $1.1%, respectively. Dariushi et al 30 investigated the effects of different parameters such as the number of layers, the type of fiber, and the presence of holes in metal layers on the time and quality of FMLs manufactured by VIP. The results showed that, increasing the number of fibrous layers, metal sheets or using woven fibers increased the infusion time, and the presence of holes in aluminum layers or using Continuous Filament Mat (CFM) fibers reduced the infusion time.…”
Section: Produces High Quality Low Void Content Hybridmentioning
confidence: 99%
“…[ 6,7 ] Therefore, the quality of the holes and the effect of the drilling process on the constituent materials become of paramount relevance, not only in terms of the potential economic losses due to the rejection or the reworking from out of tolerance or poor‐quality holes, but also in terms of the reduced reliability and safety of the structure due to weaken strength. [ 8,9 ] However, drilling of layered structure made of dissimilar materials with the scope of obtaining high quality holes, having tight tolerances and no or limited defects, can be challenging due to the different machinability of the two constituents inside the FML. [ 10–12 ] While the drilling of metal laminates is well known and optimized, even for hard‐to‐machine alloys, such as titanium‐based ones, [ 13 ] the issues arise in the machining of carbon/glass composite.…”
Section: Introductionmentioning
confidence: 99%